Aspectos lingüísticos de la evangelización del Perú en los Comentarios Reales de los Incas - Huamanchumo de la Cuba, Ofelia (Mercurio Peruano, 2020)
Approach the treatment by the Inca Garcilaso de la Vega of communication problems generated during the Spanish conquest of Peru. Among them it is remarkable the matter of the domain of Quechua language, in which Garcilaso adopts the ideas of Antonio de Nebrija on language as an instrument of unity and authority. The full command of the language and its nuances is presented as vital for the evangelization of the Indians, which reverts to a certain cultural syncretism. Finally, review the interpretation of the quipu, role and persistence present in the actual comments.